A randomized control study of oral itraconazole versus itraconazole with terbinafine in the treatment of dermatophytosis - Divya Sharma; Amandeep Saluja; Sanjay Meena; Kalpana Gupta (Wolters Kluwer Medknow Publications, 2023)
Background: Dermatophyte infections are one of the first known fungal infections of humankind and are most common throughout the world. The antifungal therapies over the past 30 years have improved, but the phenomenon of antifungal resistance is still of major concern. Combination therapies can show great promise in overcoming this problem to broaden the spectrum of activity, enhance the rate or extent of killing, and minimize the development of resistance. Objectives: To find out the therapeutic efficacy of itraconazole versus itraconazole with terbinafine for the treatment of dermatophytosis. Materials and Methods: A prospective study was conducted for a duration of 1 year on 64 patients diagnosed with dermatophytosis and was randomly divided into two groups. Group A was given oral itraconazole whereas Group B received oral itraconazole and oral terbinafine for 4 weeks along with levocetirizine daily for 2 weeks and miconazole 2% topically for 6 weeks. The measurability criteria were done on detailed clinical examination (itching, erythema, size, number, scaling, and margin) and through photographic assessment. Results: The mean difference and standard deviation of total scores for group A were 10.12 ± 4.09 and for group B were 9.94 and 3.75, respectively. The P value was not significant (P = 0.78). Out of 64 cases, 3 (5%) patients complained of gastric discomfort, 2 (3%) patients complained of nausea, and 1 (1%) of dizziness. Conclusion: This study revealed that there was a highly significant improvement in both groups with no significant difference in their clinical criteria.